2012
DOI: 10.1016/j.trsl.2012.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of electron transport before ischemia protects mitochondria and decreases myocardial injury during reperfusion in aged rat hearts

Abstract: Myocardial injury is increased in the aged heart following ischemia and reperfusion (I-R) in both humans and experimental models. Hearts from aged 24 mo. old Fischer 344 rats sustain greater cell death and decreased contractile recovery after I-R compared to 6 mo. adult controls. Cardiac mitochondria incur damage during I-R contributing to cell death. Aged rats have a defect in complex III of the mitochondrial electron transport chain (ETC) localized to the interfibrillar population of cardiac mitochondria (IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…Further, mice lacking specific miRNAs, including miR-378, exhibit enhanced mitochondrial fatty acid metabolism and elevated oxidative capacity 22 . Though increasing evidence indicates that mitochondrial subpopulations are differentially influenced by physiological stressors 4, 2326 , no study has reported specific enrichment patterns of mitomiRs in spatially-distinct subpopulations or whether distribution patterns are influenced by pathological states, including diabetes mellitus. The results of our studies suggest a dynamic system requiring the presence of RISC constituents in the mitochondrion, which function to regulate the mitochondrial genome during diabetic insult in a spatially-distinct manner.…”
Section: Introductionmentioning
confidence: 99%
“…Further, mice lacking specific miRNAs, including miR-378, exhibit enhanced mitochondrial fatty acid metabolism and elevated oxidative capacity 22 . Though increasing evidence indicates that mitochondrial subpopulations are differentially influenced by physiological stressors 4, 2326 , no study has reported specific enrichment patterns of mitomiRs in spatially-distinct subpopulations or whether distribution patterns are influenced by pathological states, including diabetes mellitus. The results of our studies suggest a dynamic system requiring the presence of RISC constituents in the mitochondrion, which function to regulate the mitochondrial genome during diabetic insult in a spatially-distinct manner.…”
Section: Introductionmentioning
confidence: 99%
“…ROS leads to damage of cell membranes, protein, DNA, and mitochondrial membrane potential (ΔΨm) [7]. The latter causes uncoupling and subsequently leads to hyperactivity of the ETC due to inefficient adenosine triphosphate (ATP) production [8,9]. Reduced ATP causes inhibition of the ATP-dependent sodiumpotassium pump (Na + -K + -ATPase), which further contributes to myocardial sodium loading [10].…”
Section: Introductionmentioning
confidence: 99%
“…Amobarbital given before ischemia also decreases cardiac injury in aged rat hearts measured after reperfusion [36]. These findings suggest that direct manipulation of mitochondrial function is an alternative approach to protect aged hearts that lack effective endogenous cytoprotective mechanisms.…”
Section: Introductionmentioning
confidence: 99%